Fine-Grained High-Permeability Fe73.5−xB9Si14Cu1Nb2.5Mx (M = Mo or W) Nanocrystalline Alloys with Co-Added Heterogeneous Transition Metal Elements - Su-Bong An; Hyun-Ah Im; Young-Tae Kwon; Jung-Woo Lee; Jae-Won Jeong (Metals)
This study investigates the effects of multi-transition metals on the soft magnetic properties of Fe73.5−xB9Si14Cu1Nb2.5Mx (M = Nb, Mo, and W) nanocrystalline soft magnetic alloys. Nanocrystalline soft magnetic materials are utilized in electronic components on the basis of their permeability and low core loss. In conventional alloys such as FINEMET, Nb inhibits nanocrystal growth and promotes amorphous formation. In this research, Mo and W were used as additional transition metals to control the size of nanocrystals and explore the potential for enhancing soft magnetic properties. We confirmed that the addition of Mo and W reduced the nanocrystal size, and the activation energy for nanocrystal formation and growth showed significant benefits for nanocrystalline alloys. Consequently, the soft magnetic properties of the alloys containing Mo and W exhibited higher permeability and lower coercivity. These results suggest that multi-transition metals are effective in improving soft magnetic properties by inhibiting nanocrystal formation and growth.